MODEL PENGELOLAAN DANA DESA DAN PEMBERDAYAAN PETANI DI DESA PERBATASAN INDONESIA DENGAN TIMOR LESTE - Boanerges Putra Sipayung; Theodorus Fobia; Werenfridus Taena; Umbu Joka (Analisis Kebijakan Pertanian, 2021)
Village funds allocation has been provided to village government by central government starting in 2015. The provision of village funds aims at ingreasing equitable development in urban areas. This study aims to design a model of implementation of village funds management and farmer empowerment, with a case of Manusasi Village, Timor Tengah Utara Distict, bordering with Timor Leste. This research was conducted in August-September 2020. The methods used in this research were quantitative descriptive analysis and SEM based on variance, namely Partial Least Square (PLS). The sampling method used in this study was accidental sampling, with the chosen sample of 75 households from the total popultation 258 huosehold farmers. Results of this study indicated that planning had a significant effect on the evaluation process of village funds. The multiplier effect value of village funds in Manusasi Village was 1.39. There was no direct effect between physical capital, social capital, and human capital on the empowermeny of farming community in Manusasi Village. An important component of the implementation model of village fund management and farmer empowerment is the socialisation of the use of village funds which aims to increase public knowledge about village funds and build partnerships with universities or other institutions as sources of experts. The role of experts is to help improve village fund management and improve the quality of programs and planning.